ANALISIS EFEK KARBON DIOKSIDA (CO2) TERHADAP KENAIKAN TEMPERATUR DI BUKIT KOTOTABANGTAHUN 2005 – 2009 - Dwi Pujiastuti (Jurnal Ilmu Fisika (JIF), 2010)
Analysis of radiative forcing of carbon dioxide (CO2) by using IPCC (Intergovermental on Panel Climate Change) method over Bukit Kototabang (Agam, West Sumatera) for period of 2005 to 2009 has been conducted. The result is correlated with temperature deviation which measured by using AWS (Automatic Weather Station). Result showed that CO2 concentration increased from 375.256 ppm in 2005 to 381.736 ppm in 2009 but still below the global CO2 concentration in every year. In addition, CO2 radiative forcing has derived increased from 1.605 Wm-2 in 2005 to 1.697 Wm-2 in 2009 but still below the global CO2 radiative forcing. Concentration of CO2 has the same trend with CO2 radiative forcing. Temperature deviation was influenced by CO2 radiative forcing but with low correlation coefficient, about 6.9%. It can be concluded that the CO2 radiative forcing is not the main factor which is influences the temperature deviation in Bukit Kototabang.